The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fphar.2020.00145
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants and Phytochemicals for the Treatment of Pulmonary Hypertension

Abstract: Background: Pulmonary hypertension (PH) is a progressive disease that is associated with pulmonary arteries remodeling, right ventricle hypertrophy, right ventricular failure and finally death. The present study aims to review the medicinal plants and phytochemicals used for PH treatment in the period of 1994-2019. Methods: PubMed, Cochrane and Scopus were searched based on pulmonary hypertension, plant and phytochemical keywords from August 23, 2019. All articles that matched the study based on title and abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 157 publications
0
12
0
1
Order By: Relevance
“…Several studies have reported that medicinal plants, nutraceuticals, and phytochemicals exert significant benefits for PAH [15]. These natural compounds have anti-inflammatory, antiproliferative, and anti-vascular remodeling properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that medicinal plants, nutraceuticals, and phytochemicals exert significant benefits for PAH [15]. These natural compounds have anti-inflammatory, antiproliferative, and anti-vascular remodeling properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ISO promotes lipolysis in the myocardium (Jasemi et al, 2020, andIpseeta et al, 2004). Lipolysis results in the release of a large amount of free fatty acids and TAG.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier references have shown that the plant preparations have anti-inflammatory (Boehm et al, 2000), anti-cancer, anti-stress, and immunomodulatory activities. WS has also shown reports of the central nervous system (CNS), endocrine (Subasini et al, 2007), and cardiovascular (Jasemi et al, 2020) diseases. Furthermore, WS preparations are thought to affect GABAergic (gamma-aminobutyric acid (GABA) (Dar et al, 2016) or cholinergic (Kumari et al, 2020) neurotransmission, which could be associated to a variety of CNS disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Many medicinal plants and natural compounds have beneficial effects in the treatment of PAH [ 63 ]. Interestingly, these compounds do not have more side effects than chemical drugs [ 64 ]. In humans, the oral administration of quercetin did not show any adverse effects at doses up to 730 mg per day over one month [ 65 ].…”
Section: Nutraceutical In the Treatment Of Cardiovascular Diseasementioning
confidence: 99%